Going IT alone : the handbook for freelance and contract software developers : a detailed guide to self-employment for software and web developers–from identifying your target market, through to managing your time, finances, and client behavior /: the handbook for freelance and contract software developers : a detailed guide to self-employment for software and web developers–from identifying your target market, through to managing your time, finances, and client behavior. (2016) - Brown, Leon (software developer)
No abstract available